CROSSED CEREBELLAR DIASCHISIS IN A CHILD WITH STATUS EPILEPTICUS: AN UNUSUAL PRESENTATION - Talha,; Mian Ayaz ul Haq,; Hira Ishaq,; Tanveer Fatima,; Aamir Khan, (Journal of Ayub Medical College Abbottabad, 2021)
Crossed Cerebellar Diaschisis (CCD) describes a depression of oxidative metabolism and blood flow in the cerebellum secondary to a supratentorial lesion in the contralateral cerebral hemisphere. The pathophysiology is not clear but appears to be caused by abnormal neuronal connection of the primary to the remote site. The diagnosis is usually done using positron emission tomography (PET) and single-photon emission CT (SPECT) scans. Almost all the reported cases of CCD are caused by acute ischemic stroke in adults. Hence, CCD secondary to status epilepticus, extremely rare and there is limited literature available on it. This is important because it's findings can easily be confused with acute ischemic stroke and similar concurrent diseases. Correct diagnosis can also help localize the cause of the seizures and significantly influence surgical decisions. We present a case of CCD in a child with status epilepticus using MRI of the brain with DWI.